Subsequent Event Risk in Individuals With Established Coronary Heart Disease - Patel, Riyaz S; Tragante, Vinicius; Schmidt, Amand F; McCubrey, Raymond O; Holmes, Michael V; Howe, Laurence J; Direk, Kenan; Åkerblom, Axel; Leander, Karin; Virani, Salim S; Kaminski, Karol A; Muehlschlegel, Jochen D; et al. (Circulation. Genomic and precision medicine, 2019)
BACKGROUND: The Genetics of Subsequent Coronary Heart Disease (GENIUS-CHD) consortium was established to facilitate discovery and validation of genetic variants and biomarkers for risk of subsequent CHD events, in individuals with established CHD. METHODS: The consortium currently includes 57 studies from 18 countries, recruiting 185 614 participants with either acute coronary syndrome, stable CHD, or a mixture of both at baseline. All studies collected biological samples and followed-up study participants prospectively for subsequent events. RESULTS: Enrollment into the individual studies took place between 1985 to present day with a duration of follow-up ranging from 9 months to 15 years. Within each study, participants with CHD are predominantly of self-reported European descent (38%-100%), mostly male (44%-91%) with mean ages at recruitment ranging from 40 to 75 years. Initial feasibility analyses, using a federated analysis approach, yielded expected associations between age (hazard ratio, 1.15; 95% CI, 1.14-1.16) per 5-year increase, male sex (hazard ratio, 1.17; 95% CI, 1.13-1.21) and smoking (hazard ratio, 1.43; 95% CI, 1.35-1.51) with risk of subsequent CHD death or myocardial infarction and differing associations with other individual and composite cardiovascular endpoints. CONCLUSIONS: GENIUS-CHD is a global collaboration seeking to elucidate genetic and nongenetic determinants of subsequent event risk in individuals with established CHD, to improve residual risk prediction and identify novel drug targets for secondary prevention. Initial analyses demonstrate the feasibility and reliability of a federated analysis approach. The consortium now plans to initiate and test novel hypotheses as well as supporting replication and validation analyses for other investigators.
Keywords: dospělí; Smoking; Female; Age Factors; Adult; ženské pohlaví; kouření; koronární nemoc; věkové faktory; lidé; Coronary Disease; prognóza; Risk Factors; Sex Factors; proporcionální rizikové modely; Male; Aged; sexuální faktory; Proportional Hazards Models; rizikové faktory; Prognosis; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans